THE CORRELATION BETWEEN FAMILY INCOME AND EDUCATION LEVEL WITH STUNTING INCIDENCE - Saadah Handayani (Lppm Unan, 2024)
Background: According to the 2005 WHO reference, stunting (short stature) is a type of malnutrition defined based on height-for-age, as measured by standard deviations. The height-for-age (HAZ) indicator identifies long-term nutritional issues caused by factors such as poverty, poor lifestyle, inadequate care, insufficient nutrition at birth, and low child height. These determinants include basic criteria like the mother's education level and economic capacity, as well as intermediary factors like family size, the mother's height and age, and the number of children, all contributing to growth delays. Objective: To investigate the correlation between stunting incidence and family income and education level in children aged 24 to 60 months. Method: This research was conducted observationally using a casecontrol study design. Data collection took place in December 2023. The sample size included 323 stunted children aged 0 to 60 months, with 64 respondents, including children with and without developmental disabilities, aged 24 to 60 months, in Paduraksa Health Center, Pemalang Regency. A purposive sampling technique was used. Univariate analysis was conducted with frequency distribution regarding family income and education level, and bivariate analysis using chi-square test. Results: Family income for most stunted toddlers was below the regional minimum wage (UMR) for 26 respondents (81.3%), while family income for most non-stunted toddlers was above or equal to the UMR for 22 respondents (66.8%). Regarding education level, it was found that most mothers of stunted toddlers (22 respondents, 68.74%) had a basic education level, while most mothers of non-stunted toddlers (20 respondents, 62.50%) had a higher education level. There was a significant relationship between family income and stunting incidence, with a p-value of 0.028. However, there was no significant relationship between education level and stunting incidence (p-value =0.660).